Resource allocation in network of workstations (NOW) - Ng, Hu Chong. (2008)
With the emergence of fast network switches, high bandwidth network, and the decreasing cost of workstations, a Network of Workstations (NOW) is becoming a viable alternative to Massively Parallel Processors (MPP) system for the execution of parallel real-time tasks. A Network of Workstations, which offers a rich source of computing power and efforts, has been expanded to tap this underutilized resource. The challenge is to develop an efficient scheduling algorithm to distribute tasks that can be executed in parallel on heterogeneous processors.